BIOM-17. BRAF MUTATION IS AN EARLY EVENT IN THE EVOLUTION OF A SUBSET OF GLIOBLASTOMAS AND IS ASSOCIATED WITH INCREASED PD-L1 EXPRESSION. (9th November 2020) - Walsh, Kyle; Xiu, Joanne; López, Giselle; Landi, Daniel; Reitman, Zachary; Mittal, Sandeep; Brenner, Andrew; Fonkem, Ekokobe; Kesari, Santosh; Phuphanich, Surasak; Newton, Herbert; Pandey, Manjari; et al.
Abstract: INTRODUCTION: BRAF is a RAF-family kinase that regulates MAPK/ERK signaling. Activating BRAF mutations, including V600E, are common in circumscribed low-grade gliomas of childhood and young adulthood, but are uncommon in infiltrative astrocytomas, including glioblastoma. Their role in glioblastoma initiation and progression requires analysis of large datasets given the low frequency (1.0%) in TCGA IDH-wild-type glioblastomas. METHODS: Molecular profiling was done on 4679 FFPE gliomas by next-generation sequencing at Caris Life Sciences, of which 3170 underwent RNA-sequencing for gene fusion and 4603 DNA-sequencing for mutations. MGMT promoter methylation was tested by pyrosequencing and PD-L1 IHC was performed using the SP142 clone. RESULTS: Excluding variants of uncertain significance, BRAF mutations/fusions were most common in pleomorphic xanthoastrocytoma (PXA; N=12/24, 50%), glioneuronal tumors (N=6/13, 46%), pilocytic astrocytoma (PA; N=15/48, 31%), and ganglioglioma (n=5/18, 28%). BRAF fusions were uncommon (N=17), most frequent in PA (N=8/31, 26%) where they were associated with older age at daignosis (P=0.043), and typically involved KIAA1549 as fusion partner (70%). BRAF-mutated/fused glioblastoma patients (N=59/3126, 2%) were younger than BRAF-wild-type glioblastoma patients (54 versus 59 years, P=3.5x10 -3 ); more likely to be MGMT -unmethylated (75% versus 56%, P=5.0x10 -3 ); and 3x more likely to express PD-L1 (55% versus 17%, P=2.1x10 -10 ). In tumors harboring a V600E mutation, the variant allele frequency (VAF) was similar in glioblastoma as in PXA, PA, ganglioglioma, and glioneuronal tumors (median VAF=35%). CONCLUSIONS: BRAF -mutated glioblastoma were 3x more likely to express PD-L1 than BRAF -wild-type glioblastoma. We observed no differences in BRAF V600E clonality in BRAF -mutated glioblastoma compared to BRAF -mutated PXA, PA, ganglioglioma, and glioneuronal tumors, suggesting BRAF mutation is an initiating event in the clonal evolution of a subset of glioblastoma. There is rationale to evaluate combined BRAF inhibition with checkpoint inhibition in BRAF -mutated glioblastoma, potentially synergizing the complete response profile of the former with the durable response profile of the latter.